2017
DOI: 10.1016/j.urology.2017.02.056
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' Perceptions of Factors Influencing the Treatment Decision-making Process for Men With Low-risk Prostate Cancer

Abstract: Objective To assess physicians’ attitudes regarding multiple factors that may influence recommendations for AS vs. AT given the central role physicians play in the treatment-decision making process. Methods We conducted semi-structured interviews to assess factors that physicians consider important when recommending AS vs. AT, as well as physicians’ perceptions of what their patients consider important in the decision. Participants included urologists (N=11), radiation oncologists (N=12), and primary care ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…Earlier interviews of prostate cancer patients in the UK found that men often felt considerable pressure from family, as well as from doctors and support groups, to pursue curative treatment [ 14 ]. A recent focus group study of physicians found that, even with the increase in recommendations of AS/WW as a treatment strategy, most family members and spouses were more often in support of active treatment and opposed to AS [ 20 ]. Our recent focus group study found that men and their partners often felt it was necessary to justify their AS decision to their social support, particularly to alleviate the fears of family and friends about their untreated cancer [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier interviews of prostate cancer patients in the UK found that men often felt considerable pressure from family, as well as from doctors and support groups, to pursue curative treatment [ 14 ]. A recent focus group study of physicians found that, even with the increase in recommendations of AS/WW as a treatment strategy, most family members and spouses were more often in support of active treatment and opposed to AS [ 20 ]. Our recent focus group study found that men and their partners often felt it was necessary to justify their AS decision to their social support, particularly to alleviate the fears of family and friends about their untreated cancer [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since mortality is essentially the same for each treatment [ 4 ], experts recommend that treatment choice should be responsive to patient preferences [ 5 ]. These personal preferences have been shown to be shaped by a patient's own beliefs, personality traits [ 6 8 ], and the people that he interacts with during the decision-making process [ 7 , 9 20 ], though many of these studies were performed in majority white populations. Understanding how men's personality traits and social influences impact the treatment decision-making process in a diverse population is important for physicians and other healthcare professionals to provide the best support possible for individual patients as they choose the best treatment for their unique circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…The findings identified a patient and family preference for curative treatment that is documented elsewhere ( Davis et al, 2017 ; Showalter, Mishra, & Bridges, 2015 ; Srirangam et al, 2003 ). Clinicians recognize the role family members play in influencing patients’ decisions about AS, and this research confirms the need to explore the best ways to achieve guideline-concordant care for patients amidst various relational and emotional pressures ( Showalter et al, 2015 ).…”
Section: Discussionmentioning
confidence: 74%
“…Clinicians’ knowledge and attitudes, the quality of the doctor-patient relationship, shared DM, and the presence of different professionals may indeed affect decision regarding and adherence to AS, as well as reduce decisional regret and distress after choice ( 50 ). Furthermore, patient and clinician preferences, the healthcare setting, and family or spouse factors have the potential to influence professionals’ treatment recommendations for men with low-risk PCa ( 50 , 51 ). Therefore, training healthcare professionals from different disciplines to work together to support a shared DM process and to make patients and families feel engaged with DM and overall care can be a key effort that still needs to be approached and researched ( 52 ).…”
Section: Discussionmentioning
confidence: 99%